Dealing with jamming in wireless sensor network - Babu, Md. Shanawas; Hossen, Md. Fahmidur (BRAC University, 2011)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2005.